To love otherwise: essays in Bible philosophy and ethics - Burggraeve, Roger (Peeters, 2020)
A philosophical reading of Scripture, that is what you will find in this book. The assumption underlying this is that the Bible itself gives rise to an original thought. The hermeneutic inspiration for this comes from Emmanuel Levinas? Talmudic philosophy. A philosophy that takes a contextual approach of Scripture seriously but also transcends it. Concretely, this reflective intention looks within the biblical text for anthropological, ethical and metaphysical insights that can be discussed and made communicable to everyone (kat' holon).00After the first chapter, the one that searches for the possibility and the proper nature of a philosophical reading of Scripture, this hermeneutical tool is applied to several narratives from the First and Second Testament00The philosophical reading of each of these narratives challenges not only Christians in their faith seeking understanding and dialogue, but also all other people to take the Bible seriously and look in it for inspiration to humanize civilization